The Point Is to Change It! Introduction to Critical Political Interventions in Media and Communication Studies - Sašo Slaček Brlek; Jernej Amon Prodnik; Bogdan Osolnik (tripleC: Communication, Capitalism & Critique)
The intention of this paper is to provide a historical overview and an introduction to the interviews with Bodgan Osolnik, Breda Pavlič, Cees Hamelink, Daya K. Thussu, Peter Golding and Dan Hind presented in this special section. Following Marx, we entitled the section The Point Is to Change It! Critical Political Interventions in Media and Communication Studies. We discuss the need for critical theory to bridge the divide between theory and practice because this notion is central to all of the interviews in one way or another. We also provide a historical contextualization of important theoretical as well as political developments in the 1970s and 1980s. This period may be seen as a watershed era for the critical political economy of communication and for the political articulation of demands for a widespread transformation and democratization in the form of the New World Information and Communication Order initiative. We believe that many contemporary issues have a long history, with their roots firmly based in this era. The historical perspective therefore cannot be seen as nostalgia, but as an attempt to understand the historical relations of power and how they have changed and shifted. In our view, the historical perspective is crucial not only for understanding long-lasting historical trends, but also to remind ourselves that the world is malleable, and to keep alive the promises of the progressive struggles of the past.